Fatherless in indonesia and its impact on children’s psychological development - Ashari, Yulinda (Fakultas Psikologi Universitas Islam Negeri Maulana Malik Ibrahim, 2018)
The power of the child's personality is the result of good parenting and handling by both of parents. If one is absent, there will be an imbalance to child psychological development. The fatherless concept itself can be interpreted as the absence of a father figure in the nurturing process. Then known the